2002
DOI: 10.1161/01.cir.0000023532.98469.48
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Depletion by Clodronate-Containing Liposomes Reduces Neointimal Formation After Balloon Injury in Rats and Rabbits

Abstract: Background-Inflammation is critical to vascular repair after mechanical injury. Excessive inflammation enhances neointimal formation and restenosis. We examined whether transient systemic inactivation of macrophages at the time of vascular intervention could attenuate the degree of expected restenosis. Methods and Results-Liposomal clodronate (LC) inhibited the growth of cultured macrophages but had no effect on endothelial or smooth muscle cells and suppressed neointimal hyperplasia in hypercholesterolemic ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

13
185
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 217 publications
(200 citation statements)
references
References 29 publications
13
185
0
Order By: Relevance
“…In contrast, events and phenomena that promote systemic inflammation, though not directly related to vascular injury, can exacerbate the reactivity to local vascular injury. We have previously shown, that induction of moderate systemic inflammation with the injection of low-dose LPS increases neointimal formation following superficial and deep vascular injury [9].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…In contrast, events and phenomena that promote systemic inflammation, though not directly related to vascular injury, can exacerbate the reactivity to local vascular injury. We have previously shown, that induction of moderate systemic inflammation with the injection of low-dose LPS increases neointimal formation following superficial and deep vascular injury [9].…”
Section: Introductionmentioning
confidence: 96%
“…Elevated inflammatory markers such as total leukocyte count [3,4] and C-reactive protein levels [5,6] are associated with worse outcome after percutaneous coronary artery interventions (PCI). Suppression of innate immunity by various strategies alleviates the inflammatory response following injury and suppresses excessive reactivity, as evidenced by lesser degree of neointimal formation [7][8][9][10]. In contrast, events and phenomena that promote systemic inflammation, though not directly related to vascular injury, can exacerbate the reactivity to local vascular injury.…”
Section: Introductionmentioning
confidence: 99%
“…1 In addition, macrophages and macrophage-derived foam cells significantly contribute to the neointimal tissue and further aggravate the local inflammatory response and neointimal growth by expression of cytokines and growth factors, especially in the context of hypercholesterolemia. [2][3][4] After endothelial denudation and apoptosis of medial SMCs, leukocyte recruitment by densely aggregated platelets and proliferation of SMCs occur at the injury site. 1,5 Ongoing monocyte recruitment during neointima formation is supported by neointimal SMCs or activated endothelium, depending on the status of reendothelialization.…”
mentioning
confidence: 99%
“…3,4 We recently showed that transient macrophage depletion reduces experimental neointimal formation after balloon injury in rats and rabbits. 5 Stent deployment profoundly alters vascular repair, and the role of innate immunity in late restenosis is further stressed. Although recoil and remodeling are negligible, local inflammation and regional neointimal formation are greater than that observed after balloon angioplasty.…”
mentioning
confidence: 99%
“…11,12 The in vitro effects of liposomal BPs (LBPs) are limited to cells with phagocytic capacity (ie, macrophages), with no effect on smooth muscle cells (SMCs) and endothelial cells. 5 Depletion of macrophages and circulating monocytes in vivo can be achieved by liposome-mediated intracellular delivery of BPs, which inactivate and kill these cells after effective phagocytosis but are not toxic to nonphagocytic cells. 5,13,14 The present study investigated whether systemic transient depletion of monocytes and macrophages by LBPs inhibits in-stent neointimal formation in hypercholesterolemic rabbits and whether inhibition of neointimal SMC growth is as potent as macrophage suppression.…”
mentioning
confidence: 99%